PENGELOLAAN KEUANGAN PADA UNIT BISNIS RUMAH MAKAN DAN PRODUK MINUMAN LEMON PONDOK PESANTREN SISWA PONPES ROJAUL HUDA YPI DARUN NASYA LEMBANG KABUPATEN BANDUNG BARAT - Windi Novianti (Jurnal Pengabdian Kepada Masyarakat, 2022)
Financial difficulties will arise if there is an error in financial management. With proper financial management, the standard of living of the community is expected to increase as well, due to the high level of a person’s income ut without proper financial management, financial security will definitely be difficult to achieve. The need for education to the public on financial products, both bank and non bank, is very urgent so that people are not easily deceived by irresponsible parties. This activity aims to make business managers understand that managing finances needs to be done in their personal lives as well as in running a business, so that they understabnd why they need to manage finances, and what benefits they will receive later when they have managed their finances well. This activity is carried out by conducting a literature study on financial management, determining the location of community service, determining the implementation time and duration of service activities, determining and preparing materials to be delivered in community service activities, delivering material on financial management in the form of materials and illustrations regarding financial management. The resukt of this activity is that students and financial managers can find out how to manage finances by making financial reports. The conclusion of this activity is that foinancial management training is a very important activity, it is hoped that students and managers can manage finances well.